1993
DOI: 10.1159/000154138
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Some Point Mutations in the Phenylalanine Hydroxylase Gene of Phenylketonuria Patients from the Moscow Region

Abstract: Thirty-one unrelated phenylketonuria patients from the Moscow region were screened for mutations in the phenylalanine hydroxylase gene at the following codons: 408, 158, 261 and IVS-12. For detection of point mutations, polymerase chain reaction amplification was applied with allele-specific oligonucleotide hybridization. The following mutation frequencies were determined: codon 408 – 56.4%; codon 158 – 8.1%; codon 261 – 3.2%, and IVS-12 – 16%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…This is consistent with the fact that most part of Latvian PKU patients have the classical form of the disease. These results show a high degree of homogeneity in the molecular basis of PKU in Latvia in agreement with what found in other populations from Eastern and Central Europe (Charikova et al, 1993;Jaruzelska et al, 1993;Lillevali et al, 1996;Giannattasio et al, 1997;Kozak et al, 1997).…”
Section: Resultssupporting
confidence: 91%
“…This is consistent with the fact that most part of Latvian PKU patients have the classical form of the disease. These results show a high degree of homogeneity in the molecular basis of PKU in Latvia in agreement with what found in other populations from Eastern and Central Europe (Charikova et al, 1993;Jaruzelska et al, 1993;Lillevali et al, 1996;Giannattasio et al, 1997;Kozak et al, 1997).…”
Section: Resultssupporting
confidence: 91%
“…The frequency of the R408W mutation among 31 unrelated PKU patients from the Moscow region (Charikova et al 1993) was comparable to that found in the present investigation. They found that the R158Q and R261Q mutations were at low frequencies; however, the IVS12nt-1 mutation was more prevalent.…”
Section: Discussionsupporting
confidence: 89%
“…To date, more than 300 PKU mutations have been reported in the world (Nowacki et al 1998). Although the molecular lesions present in the PAH genes have previously been determined among Russian populations in Moscow and Saint Petersburg (Charikova et al 1993, Baranovskaya et al 1996, little is known regarding the molecular basis of PKU in the Far East of Russia. The ethnic background in the region is predominantly Slavic (90% of the population), that originated in European Russia or in Eastern European countries.…”
Section: Introductionmentioning
confidence: 99%
“…Relative R408W-H2 frequencies of up to 84% were found in the Baltic states [Lillevali et al, 1996;Kasnauskiene et al, 2003;Pronina et al, 2003]. There are incomplete data sets for the European part of Russia and other states of the former Soviet Union [Charikova et al, 1993;Baranovskaya et al, 1996]; recent data from the Ukraine have been published in abstract format [Nechyporenko and Livshits, 2002]. Apart from a high frequency of R408W-H2, PKU is quite heterogeneous in the Czech Republic [Kozak et al, 1997].…”
Section: Eastern Europementioning
confidence: 99%